Restoring arid ecosystems: the synergistic benefits of fly ash and bentonite soil amendments - Wang, Yao; Liu, Yingzhen; Xu, Denghui; Jin, Lijuan; Xu, Zhonglin; Yang, Jianjun (Frontiers in Environmental Science, 2025)
Fly ash and bentonite, two abundant industrial by-products in China, offer promising potential for ecological restoration in arid regions. In this study, we conducted a factorial pot experiment with 24 treatment combinations (6 fly ash levels: F0–F5 = 0–100%; 4 bentonite levels: P0–P3 = 0–70 g kg-1) to evaluate their synergistic effects on two xerophytic shrubs, Lycium ruthenicum and Ephedra intermedia. A total of 600 seeds per species were sown (5 seeds × 5 replicates × 24 treatments), and plant performance was assessed based on germination rate, survival rate, plant height, dry mass, and root morphological traits. Results showed species-specific and dosage-dependent responses. For L. ruthenicum, the highest germination rate (76%) was observed under 80% fly ash without bentonite (P0F4), but biomass and root development declined under higher fly ash or bentonite-only treatments (e.g., dry mass in P1F2: 10.40% ± 6.02%). In contrast, E. intermedia showed broader tolerance, with peak germination (88%) under moderate bentonite and 60%–80% fly ash (P1F3/P1F4), and optimal growth under P3F5 (root surface area: 10.18 ± 3.09 cm2; dry mass: 33.76% ± 26.53%). Two-way ANOVA revealed significant main effects and interactions between fly ash and bentonite on key traits (e.g., p < 0.001 for germination and survival in E. intermedia). Moderate fly ash addition (F2–F3, i.e., 40%–60%) with bentonite levels of 30–50 g kg-1 effectively enhanced soil water retention and promoted early-stage growth, especially in E. intermedia. This study highlights the importance of species-specific amendment strategies and demonstrates the ecological benefits of valorizing industrial by-products for arid-land revegetation.